2021
DOI: 10.1590/1806-9282.20210634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus species on apoptosis-related genes BCL2, BAX, and caspase 3 in the testes of gamma-irradiated rats

Abstract: Ionizing radiation has various applications, including uses in medicine, industry, agriculture, and research. However, ionizing radiation is accompanied by side effects in normal radiosensitive tissues. Probiotics as natural radioprotective agents can protect normal tissues from ionizing radiation. In this regard, this study aimed to investigate the effect of Lactobacillus species on apoptosis-related genes BCL2, BAX, and caspase 3 (CASP3) in the testes of gamma-irradiated rats.METHODS: A total of 30 male Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A high-fat diet induces intestinal flora disorders, resulting in testicular dysfunction and decreased spermatogenesis (Ding et al, 2020 ). In addition to this, Lactobacillus species significantly reversed testicular damage induced by gamma irradiation in rats (Changizi et al, 2021 ). Lactobacillus casei and Lactobacillus coagulans supplementation have protective effects against CCl 4 -induced testicular toxicity, thereby increasing the rate of spermatogenesis in rats (Keshtmand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…A high-fat diet induces intestinal flora disorders, resulting in testicular dysfunction and decreased spermatogenesis (Ding et al, 2020 ). In addition to this, Lactobacillus species significantly reversed testicular damage induced by gamma irradiation in rats (Changizi et al, 2021 ). Lactobacillus casei and Lactobacillus coagulans supplementation have protective effects against CCl 4 -induced testicular toxicity, thereby increasing the rate of spermatogenesis in rats (Keshtmand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, this study revealed that Gamma-radiation inhibited Bcl-2 and activated BAX and caspase-3 genes in healthy animal tissues, and Lactiplantibacillus spp. treatment was able to reverse such effects and acted as natural radioprotectors [ 44 ]. On the other hand, LP 06CC2 extract significantly suppressed cell viability of Caco2 colorectal cancer cells by inducing apoptosis through the JNK/p38 MAPK signaling system [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of Bcl‐2 and upregulation of Bax gene expression can both promote apoptosis. [ 21,35 ] Inhibition of the expression level of Bcl‐2 may induce the activation of p38, which promotes cell apoptosis. [ 36 ] An imbalance of Bcl‐2 and Bax proteins might result in the release of cytochrome C, which triggers caspase 3 and PARP activation and leads to apoptosis.…”
Section: Discussionmentioning
confidence: 99%